Characterization of resistance response of Coffea canephora genotypes to Meloiddogyne incognita (Est I2) root-knot nematode - Santos, Anderson Vieira; Rocha, Rodrigo Barros; da Silveira, Silvaldo Felipe; Teixeira, Alexsandro Lara; de Matos, Sara Inácia; Vieira Júnior, José Roberto (Coffee Science - ISSN 1984-3909, 2018)
Meloidogynose is prominent among the factors that limit yield in C. canephora in the western Amazon, Brazil. It is caused by species of “root-knot nematode”; the most important and aggressive of these species for coffee is M. incognita. The aim of this study was to assist the selection of resistant genotypes by characterizing the reaction of 32 C. canephora clones to M. incognita (Est I2). These genotypes are selected plants from the Germplasm Bank of Embrapa Rondônia of the botanical varieties Conilon, Robusta and intervarietal hybrids. The experiments were conducted under greenhouse conditions by inoculating six seedlings for each clone with 10 ml of suspension containing 5000 eggs of a pure inoculum of M. incognita. At 150 days after inoculation, evaluations were made of fresh weight of roots (FWR), total number of galls (NG), total number of eggs (NE), and the nematode reproduction factor (RF=final population/initial population). In contrast with the susceptible controls of arabica coffee (RF=1.2) and tomato plants (RF=31.3), six clones of the Conilon botanical variety, five clones of the Robusta botanical variety and eight intervarietal hybrids reacted as resistant to M. incognita, exhibiting RF < 1 and a reduced number of galls (NGmean = < 10). The clones identified as resistant in this study were integrated in the coffee breeding program in Rondônia for development of cultivars resistant to the root-knot nematode adapted to tropical conditions.